2016
DOI: 10.1111/febs.13663
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation‐deficient mutations in tissue‐nonspecific alkaline phosphatase impair its structure and function and are linked to infantile hypophosphatasia

Abstract: Tissue-nonspecific alkaline phosphatase (TNSALP) is a membrane glycoprotein with a proposed role in bone mineralization. Indeed, mutations in TNSALP have been identified in patients with hypophosphatasia (HPP), a genetic disease characterized by hypomineralization of bone and teeth and a deficiency in serum ALP activity. TNSALP has five potential N-glycosylation sites at N140, N230, N271, N303 and N430 by standard nomenclature. A mutation at one of these sites, N430, was recently detected in a patient with inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…The N - and O -glycans of glycoproteins are participated in protein folding, trafficking, function and stability [ 32 , 33 ]. The N - and O -glycan chains of AP isoforms are synthesized with various glycosidases and glycosyltransferases by adding monosaccharides in the path from the endoplasmic reticulum (ER) and Golgi apparatus to the apical membrane anchored via glycosylphosphatidylinositol (GPI) [ 30 , 59 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The N - and O -glycans of glycoproteins are participated in protein folding, trafficking, function and stability [ 32 , 33 ]. The N - and O -glycan chains of AP isoforms are synthesized with various glycosidases and glycosyltransferases by adding monosaccharides in the path from the endoplasmic reticulum (ER) and Golgi apparatus to the apical membrane anchored via glycosylphosphatidylinositol (GPI) [ 30 , 59 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The bone AP isoforms (B1, B2, and B/I) differed in N -linked glycans, which resulted in significantly different catalytic properties [ 32 ]. A study using site-directed mutagenesis shown that the dimeric structure required for TNAP activity remained in individual single N -glycan deletion mutants [ 33 ]. The infantile hypophosphatasia was linked to TNAP mutants (N430S) that were glycosylation-defective and unable to dimerize; and the N -glycans on N230, N271 and N303 were the minimal requirement for the structure, function and stable expression of TNAP in a cell [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has later been confirmed that all TNALPs are N-glycosylated and that bone and kidney ALP are O-glycosylated but not LALP [82,134]. The two sites in GCALP are occupied by N-glycans and deletion of either one, or two of these glycans, do not affect the enzymatic activity of GCALP [135].…”
Section: Posttranslational Modifications Of Alpmentioning
confidence: 94%